PEMBERIAN PAKAN STEP-DOWN PROTEIN DENGAN SUBTITUSI DEDAK PADI AMOFER TERHADAP PERFORMAN PRODUKSI DAN INCOME OVER FEED COST (IOFC) ITIK CIHATEUP: Pakan Step-Down Protein dengan Subtitusi Dedak Padi Amofer - Frasiska, Nurul; Rizqi, Kiki; Rahayu, Novia; Ardigurnita, Firgian (Jurnal Peternakan Nusantara, 2022)
This study aims to produce duck feed with complete and economical nutrient content in terms of production performance parameters and Income Over Feed Cost (IOFC). The research was conducted by experimental method using Completely Randomized Design (CRD) with 5 treatments, namely P0+: control treatment using 18% PK basal diet, P0¬˗: 16% PK basal feed treatment, P1: 16% PK Basal Feed with 10% amopheric bran. , P2: 16% PK basalt diet with 20% amopheric bran, P3: 16% PK basalt feed with 30% amofer bran. The research material used 60 DOD Cihateup Ducks. Each treatment was repeated 4 times and each experimental unit contained 3 ducks. The results of the study using step down protein feed with amofer rice bran substitution significantly decreased production performance at higher levels of amofer rice bran administration. As well as producing the best income over feed cost in the P0+ treatment, namely the control treatment using basal feed with 18% protein.